2021
DOI: 10.3390/act10070143
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Identification of BLDC Motor Using Electromechanical Tests and Recursive Least-Squares Algorithm: Experimental Validation

Abstract: In this article, the parameter identification of a brushless DC motor (BLDC) is presented. The approach here presented is based on a direct identification considering a three-phase line-to-line voltage electromagnetic torque as function of the electric currents and rotor speed. The estimation is divided into two stages. First, the electrical parameters are estimated by well-known no-load and DC tests. Consequently, estimation of mechanical parameters is performed using a recursive Least Square Algorithm. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Although GWO generated the best parametric estimation in this research, the Steiglitz-McBride algorithm could work as another alternative when the application requires low computational cost and a low standard deviation in the estimation of each parameter; see Table 8. For example, in [49], it has been shown that the Steiglitz-McBride algorithm is useful in the parametric estimation of electrical machines such as DC motors, brush DC, and brushless AC and gear machines. Also, it is frequently used as an optimizer.…”
Section: Discussionmentioning
confidence: 99%
“…Although GWO generated the best parametric estimation in this research, the Steiglitz-McBride algorithm could work as another alternative when the application requires low computational cost and a low standard deviation in the estimation of each parameter; see Table 8. For example, in [49], it has been shown that the Steiglitz-McBride algorithm is useful in the parametric estimation of electrical machines such as DC motors, brush DC, and brushless AC and gear machines. Also, it is frequently used as an optimizer.…”
Section: Discussionmentioning
confidence: 99%
“…where λ(k) is a pondered constant value for all k domain. This value is defined as the forgetting factor of the algorithm [25]. The term λ must be included inside the interval (0; 1].…”
Section: Recursive Least-square Identification Algorithmmentioning
confidence: 99%
“…Moreover, appropriate modeling for the system is carried out using algorithms such as the linear identified model, nonlinear grey-box model, nonlinear ARX model, and Hammerstein-Wiener model. Hybrid adaptive position controller design in which RLS estimator, disturbance observer and Lyapunov methods are used together [7], RLS estimator method based on a discrete-time sliding mode controller used in the control of the DC motor speed [8], and the RLS approach, which estimates the parameters of the DC motor model [9], can be given as examples to adaptive controller designs. Adaptive designs developed are also tested on other systems.…”
Section: Introductionmentioning
confidence: 99%